Characterization of the flavonolignans in Silybummarianum L. Grown Naturally in Iraqi-Kurdistan Region - NawzadSabir, Mohammed; AbdulrahmanAskari, Ali (Sulaimani Journal for Pure and Applied Sciences, 2013)
(Abstracted from MSc. Thesis entitles "Pharmacognostic and Pharmacologic study of Silybum marianum grown naturally in Iraqi-Kurdistan Region") The antihepatotoxic principles found in the indigenous plant Silybum marianum L. (Milk thistle) was obtained using a multi-extraction/ separation and isolation procedures. Starting with identification of the plant and collection of the seeds. A pretreatment (defatting) step with light petroleum ether preceded the extraction with organic solvent (ethanol) in a soxhlet extractor. The alcoholic extract after drying was partitioned with n-hexane, Chloroform, Ethyl acetate, and n-butanol successively. Each fraction was separated by flash column chromatography. The sub-fractions after column chromatography were tested with thin layer chromatography (TLC) for the presence of the flavonolignans. Fractions showed spots with the same Rf-values were combined and furthermore isolated with high performance liquid chromatography (HPLC). Components were then purified and identified using UV, IR-spectroscopy. The results were compared with a standard sample of silybin (obtained from Sigma-Aldrich Co.). Results confirmed that the plant Silybum marianum L. which grows indigenous in Kurdistan Region/ Iraq, reserves the same active components (flavonolignans) present in the plant that grows elsewhere.
Keywords: Flavonolignans; Silybins; Chromatography